CERDAS MENGGUNAKAN INTERNET DI MASA PANDEMI COVID-19 - Thresia Hilda Mathelda Yenkase Krey; Winna Amelia Alfrida Senandi (JURNAL PENGABDIAN PAPUA, 2023)
This activity is a form of application of science and technology which is carried out through counseling entitled "Smart Using of the Internet during the COVID-19 Pandemic" carried out in the Abepura GMAHK Church, PGRI Jayapura High School and Asei Kecil Village in Jayapura Regency with the target of counseling participants attending are children school age to adolescents and youth. The purpose of holding this service is to provide an understanding of the need to use the internet intelligently during the Covid-19 pandemic, various efforts to avoid cyber-crime, as well as legal sanctions related to crime in cyberspace. In the counseling activities carried out, it can be seen that the extension participants felt enthusiastic in receiving the material provided, indicated by various responses and good responses from the participants who asked questions during the counseling. It is hoped that this activity can be carried out routinely, not only for teenagers and young people, but also for parents as a form of prevention against internet abuse behavior by unwise actions such as spreading hoax news, hate speech, and fictitious transactions by unscrupulous and irresponsible actors.Ã‚Â Keywords: Cyber-crime; Cyber-ethic; Internet; Law; Youth